Analysis of Investment Factors and Decisions among Generation Z and Generation X in Indian Capital Market - Savithri, M.; Rajakumari, D. (International Journal of Economics and Financial Issues, 2024)
This study highlights the disparate behaviours, motives, and methods of these two unique generations as it investigates the investment fervour of Generation Z and Generation X in the Indian capital market. Due in large part to historical financial practices and economic volatility, Generation X favours conservative investment strategies, placing a higher value on stability and long-term growth through well-established asset classes like real estate and mutual funds. As a result of growing up in a digitally first world, Generation Z, on the other hand, has a more daring attitude when it comes to investing and is frequently drawn to high-risk chances like cryptocurrencies and Capitals that are influenced by social media trends. The study utilises a mixed-methods approach, integrating quantitative surveys and qualitative interviews to evaluate the investing choices and behaviours of 393 participants, split evenly between the two groups. The results show notable variations in financial literacy, risk tolerance, and how technology affects investment choices. The report also emphasises how crucial it is to match financial services to the distinct requirements and values of every generation, especially as Generation Z’s emphasis on ethical and sustainable investing is changing the industry. Financial institutions may build a more knowledgeable and empowered investor community by better engaging with their clients by taking into account these generational disparities.